Design Optimal Feedback Control Using Evolutionary Particle Swarm Optimization in Multi- Machine Power System - Priyadi, Ardyono; Purnomo, Mauridhy Hery; Pujiantoro, Margo (JAVA Journal of Electrical and Electronics Engineering, 2013)
This This paper proposes an application of Evolutionary Particle Swarm Optimization (EPSO) to design weighting matrices Q and R elements in Linear Quadratic Regulator (LQR) optimization process. Solving optimal feedback control has already established by LQR method. However, there still has some problem to find the weighting matrices Q and R.These weighting matrices are the most important components in LQR optimization method. Weighting matrices are calculated using trial and error, Particle Swarm Optimazation (PSO), and EPSO techniques and simulation results are compared. Static and Dynamic loads are considered and comparison is illustrated.